EFEKTIVITAS PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN GIANYAR DALAM PENGELOLAAN PASAR TRADISIONAL TAMPAKSIRING - Widya Adnyana, Sang Made; Bandiyah, Bandiyah; Winaya, I Ketut (CITIZEN CHARTER, 2019)
ABSTRACT This study examines the effectiveness of supervision of the Tampaksiring Traditional Market. This study applies descriptive qualitative. This study applies a purposive sampling technique. The results of this study are: Accurate, information about market regulations is only for internal organizations and there are no specific regulations on market supervision. Focused on strategic supervision points, the supervision of the Tampaksiring Traditional Market has not yet become a priority, focusing only on small scale supervision. On time, supervision is carried out in a timely manner so that it does not affect the quality of supervision. Flexible, supervision is static so it is unable to respond to irregularities in the market. As a guideline and operational, there is no supervision system that guides the market supervision process. So, it needs improvement so that the monitoring system is effective. Keywords: Supervision, Traditional Markets